Study of Contraceptive Management in National Health Insurance Era at Central Java (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Healthcare facilities partners of BPJS have not been synchronized with registered healthcare facilities. Empty stock of contraceptives, excessive storage of contraceptives, and disruption in distribution chain are still seen in the last three years. The purpose of this study was to identify issues related to the management of contraceptives (planning, acceptance and storage). The research used mixed method (quantitative and qualitative approach). The samples were 30 first-level healthcare facilities in Jepara and Wonosobo regencies. There was no planning at provincial level because contraceptive planning activities was regulated by the central health office. Planning of contraceptive requirement at regency/city level was conducted by provincial health office. The acceptance mechanism in the Province involved inventory officer while at health facilities it was performed by Family Planning program manager. Observation of storage rooms for contraceptive in Jepara found that there was no temperature recording device, excess stock of contraceptive injections and pills, absence of thermometer in the storage room, non-functional air conditioning, no separation between storage of hormonal and non-hormonal contraceptive, and there was no distance between pallet and the wall. Meanwhile, contraceptive storage space in Wonosobo has met the Standard Operating Procedure (SOP).